2020
DOI: 10.1021/acs.orglett.0c00440
|View full text |Cite
|
Sign up to set email alerts
|

Biosynthesis of the Prenylated Salicylaldehyde Flavoglaucin Requires Temporary Reduction to Salicyl Alcohol for Decoration before Reoxidation to the Final Product

Abstract: The biosynthetic pathway of the prenylated salicylaldehyde flavoglaucin and congeners in Aspergillus ruber was elucidated by genome mining, heterologous expression, precursor feeding, and biochemical characterization. The polyketide skeleton was released as alkylated salicyl alcohols, which is a prerequisite for consecutive hydroxylation and prenylation, before reoxidation to the final aldehyde products. Our results provide an excellent example for a highly programmed machinery in natural product biosynthesis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
34
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(35 citation statements)
references
References 29 publications
1
34
0
Order By: Relevance
“…It was discovered in the last century, but the biosynthetic pathway was only reported in 2020 [50]. In 2020, the biosynthetic gene cluster of flavoglaucin in Aspergillus ruber was proposed [40,50]. Furthermore, the comparison between the proposed BGC in E1 and the known flavoglaucin gene cluster showed that the number of genes varies enormously (16 vs. 8).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…It was discovered in the last century, but the biosynthetic pathway was only reported in 2020 [50]. In 2020, the biosynthetic gene cluster of flavoglaucin in Aspergillus ruber was proposed [40,50]. Furthermore, the comparison between the proposed BGC in E1 and the known flavoglaucin gene cluster showed that the number of genes varies enormously (16 vs. 8).…”
Section: Discussionmentioning
confidence: 99%
“…However, the similarity of PKS genes and the eight genes downstream of BGC at the amino acid level was more than 85%. In addition, A. ruber can produce six kinds of flavoglaucin and congeners, including isoaspergin, dihydroauroglaucin, aspergin, flavoglaucin, auroglaucin, and 2-(1 ,5 -heptadienyl)-3,6-dihydroxy-5-(3"-methyl-2"-butenyl) benzaldehyde [40]. However, the analysis of secondary metabolites of E. cristatum E1 found that it cannot produce the last compound, but can produce iso-dihydroauroglaucin.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Interestingly, compound 41 is also an intermolecular [4 + 2] adduct that involves the coupling of epoxycyclohexenone and α-pyrone two building blocks via the Diels–Alder addition. Recently, the biosynthetic pathways of epoxycyclohexenone-derived fungal polyketides trichoxide, sordarial, and flavoglaucin have been investigated in detail, which provide new insights into the biosynthesis of the naphthalenone unit in 41 [ 55 , 56 , 57 ]. The biosynthesis of some fungal α-pyrone-linked NPs such as alternapyrones and citreoviridin have been reported.…”
Section: Representative Fungal Nps Might Be Biosynthesized By Two Sep...mentioning
confidence: 99%